ESBL Types and Plasmid Heterogeneity in Urinary E. coli Isolates: Results From a Nationwide Multicenter Study in Croatia. (October 2020) - Mestrovic, Tomislav; Krilanovic, Marija; Tomic-Paradzik, Maja; Beader, Natasa; Herljevic, Zoran; Conzemius, Rick; Barisic, Ivan; Vranes, Jasmina; Elvedi-Gasparovic, Vesna; Bedenic, Branka
Abstract : Background: The prevalence of Escherichia coli strains producing extended-spectrum β-lactamases (ESBLs) has increased both in the community and in healthcare settings. Furthermore, recent studies in nursing homes and long-term care facilities have shown that these institutions can act as potential reservoirs of ESBL- and CTX-M–producing E. coli . Consequently, we aimed to characterize ESBLs produced by E. coli isolates causing hospital-onset, long-term care facility and community infections throughout Croatia (Europe), as well as to compare antimicrobial sensitivity patterns, molecular specificities, plasmid types and epidemiological features. Methods: From a total pool of 16, 333 E. coli isolates, 164 ESBL-producing strains with reduced susceptibility to third-generation cephalosporins were used for further appraisal. Phenotypic tests for the detection of ESBLs and plasmid-mediated AmpC β-lactamases were initially pursued (including a novel version of modified CIM test named cephalosporin inactivation method), followed by conjugation experiments, molecular detection of resistance genes, plasmid extraction with PCR-based replicon typing, serotyping, genotyping with pulsed-field gel electrophoresis, and whole-genome sequencing (WGS). Results: The isolates in this study exhibited a high level of resistance to expanded-spectrum cephalosporins and carried CTX-M or TEM β-lactamases, and all of them were classified as multidrug-resistant due to their resistance pattern to other antimicrobial drugs. The β-lactamase content did not differ among isolated E. coli strains from various sources (ie, hospitals, nursing homes, and the community). According to the genotyping results, the isolates were allocated into 8 clusters, which contained subclusters. Serotyping results revealed that O25 antigen was the dominant one; furthermore, isolates subjected to WGS belonged to the ST131 sequence type. The most pervasive plasmid types in the isolates from the country's capital (Zagreb) were IncFII and FIA, whereas FIA alone was a dominant plasmid type in the southern part of the country. Conversely, eastern parts were characterized by plasmids belonging to IncB/O and IncW groups. Conclusions: Our study demonstrated the dissemination of group 1 CTX-M–positive E. coli not only in different geographic regions of Croatia but also in different arms of the healthcare system (ie, hospitals, nursing homes, and the community). Our results also confirmed the switch from previously pervasive SHV-2 and SHV-5 ESBLs to the nationwide predominance of group 1 CTX-M β-lactamases; however, regional distribution was associated with different plasmid types carrying bla CTX-M genes. These types of nationwide studies are indispensable for informing global decision making that addresses the issue of antimicrobial resistance. Funding: None Disclosures: None